2022
DOI: 10.1007/s11845-022-02997-w
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of SARS-CoV-2 re-infection in anti-nucleocapsid IgG-positive healthcare workers: a prospective cohort study

Abstract: Background Since the pandemic of SARS-CoV-2 began, our understanding of the pathogenesis and immune responses to this virus has continued to evolve. It has been shown that this infection produces natural detectable immune responses in many cases. However, the duration and durability of immunity and its effect on the severity of the illness are still under investigation. Moreover, the protective effects of antibodies against new SARS-CoV-2 variants still remain unclear. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In a study of healthcare workers positive for anti-N antibodies, it was reported that anti-N antibodies greatly reduced the risk of re-infection for 6 months. 7 Another study reported that anti-N antibodies in COVID-19 convalescent patients persisted for over a year, with an increased response rate in the first 25-30 weeks, and that they subsequently began to decrease and remained detectable for >15 months. 8 The anti-N antibody situation in Japan suggests that the infection may spread for some time.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of healthcare workers positive for anti-N antibodies, it was reported that anti-N antibodies greatly reduced the risk of re-infection for 6 months. 7 Another study reported that anti-N antibodies in COVID-19 convalescent patients persisted for over a year, with an increased response rate in the first 25-30 weeks, and that they subsequently began to decrease and remained detectable for >15 months. 8 The anti-N antibody situation in Japan suggests that the infection may spread for some time.…”
Section: Discussionmentioning
confidence: 99%